Normal tissue homeostasis and impairment of selective inflammatory responses in dendritic cells deficient for ATF6α - Gutiérrez-Ballesteros, Francisca; Morales-Reyes, Jonathan; Fernández, Dominique; Geisse, Antonia; Arcaya, Amada; Flores-Santibañez, Felipe; Bono, María Rosa; Osorio, Fabiola (Frontiers in Cell and Developmental Biology, 2023)
The initiation of adaptive immunity relies on the performance of dendritic cells (DCs), specialized antigen presenting cells. As such, the molecular mechanisms safeguarding DC homeostasis are matter of intense research. Sensors of the unfolded protein response (UPR) of the endoplasmic reticulum, a three-pronged signaling pathway that maintains the fidelity of the cellular proteome, have emerged as regulators of DC biology. The archetypical example is the IRE1/XBP1s axis, which supports DC development and survival of the conventional type 1 DC (cDC1) subtype. However, the role of additional UPR sensors in DC biology, such as the ATF6 branch, has not been clearly elucidated. Even though Xbp1 is transcriptionally induced by ATF6 under ER stress, it is unclear if cDCs also co-opt the ATF6 branch in tissues. Here, we examine the role of ATF6 in cDC homeostasis in vivo and upon innate stimulation in vitro. In steady state, animals lacking ATF6 in CD11c+ cells display normal cDC frequencies in spleen, intestine, liver and lung. Also, ATF6 deficient cDCs express normal levels of Xbp1 mRNA and additional UPR components. However, a reduction of lung monocytes is observed in Itgax Cre x Atf6fl/fl conditional deficient animals suggesting that ATF6 may play a role in the biology of monocytes. Notably, in settings of DC activation, ATF6 contributes to the production of IL-12 and IL-6 to inflammatory stimuli. Thus, although ATF6 may be dispensable for tissue cDC homeostasis in steady state, the transcription factor plays a role in the acquisition of selective immunogenic features by activated DCs.